A REVIEW ON THE INFLUENCE OF SWIMMING ON POSTURE DEFICIENCIES - Dan Ionuț PÎRJOL; Mihaela ORAVIȚAN; Dan MONEA (Cluj University Press, 2023)
Introduction: All sports bring health benefits when practiced correctly, but swimming has, without a doubt, some special features that no other aerobic exercises have, due to the special conditions the aquatic environment requires: the position of the body, the stresses imposed on the body necessary for movement in water (floating, immersion etc.). Objectives: Through this study we want to analyze the specialized literature regarding the influence of swimming on body posture and at the same time we wish to observe the effectiveness of posture-correction interventions used and which of them had the best results. Material and method: The present study analyzed articles from the following databases: PubMed, Scopus, Google Scholar and ResearchGate published between 2013 and 2022. After applying the inclusion and exclusion criteria, 18 articles were selected for analysis. Results: According to selected studies, it was observed that swimming exercises have multiple beneficial effects on the human body, especially in people suffering from various diseases of the lumbar spine. but there are also specialist studies that underline the possible harmful effects on posture. Conclusions: Although many studies have confirmed the positive effects of swimming on postural deficiencies due to the peculiarities of the aquatic environment, more and more studies have recently emerged that contradict them. According to the latter, it is recommended that swimming should be combined with physiotherapy, therapeutic massage and/or hydrokinetic therapy in order to achieve the desired effects in the treatment of postural deficiencies. REZUMAT. Introducere: Toate sporturile aduc beneficii pentru sănătate atunci când sunt practicate corect, dar înotul are, fără îndoială, câteva particularități pe care nu le au alte exerciții aerobice, datorită condițiilor speciale pe care le impune mediul acvatic: poziția corpului, solicitările impuse corpului necesare mișcării în apă (plutire, imersiune etc.). Obiective: Prin acest studiu dorim să analizăm literatura de specialitate în ceea ce privește influența înotului asupra posturii corporale și, în același timp, să observăm eficiența diferitelor intervenții utilizate pentru corectarea posturii. Material și metodă: Au fost analizate articole din următoarele baze de date: PubMed, Scopus, Google Scholar și ResearchGate publicate între anii 2013 și2022. În urma aplicării criteriilor de includere și excludere, au fost selectate pentru analiză 18 articole. Rezultate: Conform studiilor selectate, s-a observat că exercițiile de înot au multiple efecte benefice asupra organismului uman, în special la persoanele care suferă de diverse afecțiuni ale coloanei lombare. dar există și studii de specialitate care subliniază posibilele efecte nocive asupra posturii. Concluzii: Deși multe studii au confirmat efectele pozitive ale înotului asupra deficiențelor de postură datorită particularităților mediului acvatic, au apărut, recent, din ce în ce mai multe studii care le contrazic. Conform acestora din urmă, se recomandă ca, pentru a avea efectele dorite în tratamentul deficiențelor posturale, înotul să fie asociat cu kinetoterapia, masajul terapeutic și/sau hidrokinetoterapia. Cuvinte cheie: înot, coloană vertebrală, postură, copii, deficiențe fizice, scolioză, cifoză, plan frontal, plan sagital Received 2022 November 14; Revised 2023 March 24; Accepted 2023 March 27; Available online 2023 May 30; Available print 2023 June 30.